Blood and blood-pressure in relation to the etiology, prophylaxis, treatment and cure of pulmonary tuberculosis; also suggested coincident or alternative therapeutic measures - Murray, Henry Arthur (The University of Edinburgh, 1928)
The line of thought followed in this thesis was suggested by the observation and study of a tuberculous family, details of which will be considered under the appropriate section.

Although I do see occasional cases of pneumonokoniosis ( miner's phthisis) here, true pulmonary tuberculosis is rare, and I have the greatest difficulty in persuading the natives to come into hospital unless they are acutely ill, as they wish to get back to their homes to attend to their cattle or lands.

In consequence, I have not the opportunity for clinical trial of the method herein advocated, and must therefore confine myself mostly to theoretical discussions and the drawing of logical conclusions. Tuberculosis is generally regarded as a general systemic disease, and, by many authorities, as primarily involving the lymphatic system, from whence it may spread to bones, lungs, or to any organ, but it is when the lungs become the chief seat of the disease, that the real danger to life arises, in that it gradually deprives the patient of vital organs, namely the lungs, so that he would be bound ultimately to die from want of them, if his life were not brought to an untimely end by one of the natural terminations of the disease, such as haemorrhage or toxaemic intoxication.

Up to a certain point, the disease as it affects the lungs, appears, as it progresses, to run a more and more chronic course, presumably owing to nature's protective and reparative efforts; and, but for the inevitable spread of the disease throughout the lungs, this reparative process would undoubtedly effect a cure; no less than it does when the disease manifests itself in such structures as bone or lymphatic glands, aided merely by more or less conservative treatment.

The pulmonary form of the disease is much the commonest clinically, and the cause of, by far the greatest amount of morbidity — and highest mortality — amongst the human race.

If tuberculosis of the lungs could be regarded as of no more serious moment than that of other structures, much would have been attained. This, at least, I venture to believe, is within the realms of possibility.